Tdap vaccine attitudes and utilization among pregnant women from a high-risk population. Issue 4 (2nd April 2016) - Dempsey, Amanda F.; Brewer, Sarah E.; Sevick, Carter; Pyrzanowski, Jennifer; Mazzoni, Sara; O'Leary, Sean T.
ABSTRACT: Infants infected with Bordatella pertussis experience high morbidity and significant mortality. Vaccinating pregnant mothers with the tetanus-diphtheria-acellular pertussis (Tdap) vaccine is a recommended strategy for preventing infant pertussis. This is especially important for mothers living in poverty and from racial and ethnic minority populations as these groups are at increased risk of having a pertussis-affected infant. Using the Health Belief Model as a framework, we surveyed a convenience sample of pregnant mothers representing these high-risk populations to understand factors associated with Tdap vaccine uptake during their pregnancy. Among the 316 mothers surveyed, 82% had gotten or planned to get Tdap that same day even though 63% of the sample had concerns about the safety of the vaccine during pregnancy. Perceived benefits and norms were the Health Belief Model constructs most consistently associated with Tdap vaccination. Although 32% of women reported prior Tdap vaccine receipt, this factor was not associated with Tdap vaccination during the current pregnancy, contrasting studies of vaccination done in non-pregnant populations. Important variations in attitudes were apparent, with Spanish-speaking women significantly more likely to have concerns about the vaccine's safety and efficacy than English-speaking women. This study indicates that among this high-risk population acceptance of Tdap vaccine during pregnancy is high. However, our results suggest that it may be important to modify information conveyed about the safety and importance of Tdap during pregnancy based on individual level factors such as language or acculturation.